The Influence of Supply Chain Integration on Supply Chain Performances - Yuen, Kum Fai (2015)
Integration in the shipping industry is increasingly viewed as a significant strategy to achieve responsiveness and efficiency in the transport chain. Previous research work has proposed numerous supply chain integration practices (SCIPs) for firms to achieve desired performances. However, not all practices can be directly translated into realizable benefits. It is contested that SCIPs must be industry-specific (relevant) and feasible to implement. Hence the objectives of this paper are to, firstly, select the best subset of SCI variables which explains for performance in the container shipping industry and secondly, examine the possibility of cumulative capabilities between internal and external SCI. The methodology of this research combined both qualitative and quantitative approach. Structured face-to-face interviews were first conducted on eight individuals of managerial position from the shipping industry. Thereafter, a survey was administered on 1937 maritime firms. The collected data was analysed using multiple regression technique on SPSS. The results showed that the container shipping industry is more integrated internally than externally. However, variables relating to external integration provide greater explanation for driving supply chain performances (SCPs) in the industry. It was also found that there are limited cumulative capabilities between similar variables presented in internal and external integration. This paper has contributed to the literature by establishing the link between SCI and SCP. In addition, the proposed framework in this paper could support management decisions in achieving greater performances. Future research includes expanding the current framework to incorporate other aspect of performances (i.e. financial and other non-financial performances).